1996
DOI: 10.1111/j.1600-0773.1996.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Protective Action of α‐Tocopherol in Vascular Hypoxia

Abstract: The functioning of the guinea-pig isolated portal vein was monitored by measuring spontaneous mechanical activity, responses to electrical stimulation and administered noradrenaline in normoxic conditions. The effect of hypoxia, induced by bubbling the physiological bathing solution with a 95% N(2)/5% CO(2) gas mixture, on the mechanical performance of the vein was then assessed. Spontaneous activity declined in hypoxia, with mean contraction tension reduced by 55 + or - 8.8%. The responses to electrical field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There is no information on the effect of antioxidant therapy on fetal growth in pregnancies under hypobaric hypoxia. However, different types of experiments have demonstrated the beneficial effects of antioxidant therapy on several physiological responses to HA or hypoxia (Inan et al 1995;Kelly and Richardson 1996;Tan et al 1996;Mohanraj et al 1998;Purkayastha et al 1999;Ilavazhagan et al 2001;Miura et al 2006). In addition, several studies have shown that, in pathological gestations in which oxidative stress is evident, as in preeclampsia (Chamy et al 2006) or diabetic pregnancies (Cederberg et al 2001a), vitamins C and E are successful in preventing oxidative fetal damage and improving fetal outcome (Cederberg et al 2001b;Chappell et al 2002;Rodrigo et al 2005).…”
Section: Pregnancy Outcomementioning
confidence: 99%
“…There is no information on the effect of antioxidant therapy on fetal growth in pregnancies under hypobaric hypoxia. However, different types of experiments have demonstrated the beneficial effects of antioxidant therapy on several physiological responses to HA or hypoxia (Inan et al 1995;Kelly and Richardson 1996;Tan et al 1996;Mohanraj et al 1998;Purkayastha et al 1999;Ilavazhagan et al 2001;Miura et al 2006). In addition, several studies have shown that, in pathological gestations in which oxidative stress is evident, as in preeclampsia (Chamy et al 2006) or diabetic pregnancies (Cederberg et al 2001a), vitamins C and E are successful in preventing oxidative fetal damage and improving fetal outcome (Cederberg et al 2001b;Chappell et al 2002;Rodrigo et al 2005).…”
Section: Pregnancy Outcomementioning
confidence: 99%
“…Vitamin E has a role in protecting venous smooth muscle from the hypoxia-induced depression of vascular smooth muscle contraction [10]. Other experiments, using guinea pig colonic smooth muscle, indicate that vitamin K 1 , of a length similar to vitamin E, preserves the smooth muscle functionality during hypoxia [12].…”
Section: Introductionmentioning
confidence: 98%
“…Acute hypoxia attenuates vasoconstriction in response to noradrenaline in the portal vein of guinea pigs [10], and it is also responsible for the attenuation of the contractile response elicited by noradrenaline and KCl in aorta strips of rats [2]. Furthermore, aortic strips from rabbits exhibit reduced responses to noradrenaline and adrenaline [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants may have the potential to protect cells from oxidative damage (Jelkmann et al, 1997). Antioxidants (Trolox and ascorbic acid) protect the fetal heart in rabbit fetal hypoxia (Tan et al, 1996), and vascular hypoxia (Kelly and Richardson, 1996), and ameliorate oxidative stress in PC12 cells (Chanvitayapongs et al, 1997).…”
mentioning
confidence: 99%